Inklusifitas Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Pesantren - Badrut Tamam; Muhammad Arbain (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2020)
ABSTRACTInternalization and development of the Islamic religious education curriculum in Islamic-based institutions such as Islamic boarding schools are required to have a solid foundation. The fundamental value of the development of the Islamic Religious Education curriculum is an important part of maintaining Islamic education buildings, especially in the development of inclusive pesantren. For this reason, the developer of the Islamic Religious Education curriculum needs to lay the foundation for the development of subjects to be used in Islamic boarding schools. Descriptive analysis is used to analyze in this research on the development of the Islamic religious education curriculum. Based on the results of the analysis, there are seven foundations that can be used in the development of the Islamic religious education curriculum in Islamic education institutions such as Islamic boarding schools, namely: theological foundation (religion), philosophical foundation, ideological foundation, psychological foundation, sociological foundation, science and technology foundation, and organizational foundation. By internalizing and developing these values, Islamic education institutions based on pesantren can be well